Partisipasi Masyarakat dalam Pengembangan Ekowisata di Desa Peliatan, Kecamatan Ubud - Km. Deddy Endra Prasandya; Made Wina Satria; Ni Wayan Nurwarsih (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
The research that has been conducted has concluded that many villages in Bali are likely to develop into more sustainable ecotourism. One of them is Peliatan Village in Ubud District. Based on the synthesis of ecotourism theories, there are six criteria for ecotourism development, including environmental, community participation, education, economics, socio-cultural, and institutional. The first focus of this research is to find out the importance of community participation as a criterion for ecotourism development. The second is to understand the degree of participation of the Peliatan village community in the development of ecotourism. This research is a mixed-method research, adopting AHP (Analytical Hierarchy Process) methods to form a hierarchical structure of ecotourism development criteria, in order to understand the priority of community participation as an ecotourism standard. The results show that the criterion of community participation ranks third (slightly more important, with a weight of 0.168) after the environmental standard (weight 0.281) and social culture (0.210). Residents of Peliatan Village participate in each of the activities in their village (planning, development, management, monitoring/evaluation), which plays a very important role in the development of Peliatan Village's ecotourism.